South Africa's debt sustainability: A multi-factor approach - Begbie, Lyle (School of Economics, 2023)
An increasing debt-GDP ratio, slow growth, high debt costs and declining credit ratings call into question the sustainability of South Africa's public debt. However, some commentators have drawn on Modern Monetary Theory in arguing that increasing debt can be tolerated for states that have a level of monetary sovereignty. This paper concludes that South Africa has a high degree of monetary sovereignty due to factors including its flexible exchange rate, independent and credible central bank, high level of financial development and private wealth and limited liquidity risk. However, the scope for increasing debt is not unlimited, the risks associated with rising inflation cannot be ignored and the national treasury's fiscal consolidation plan should not be abandoned. South Africa's comparatively strong financial institutions and persistently low global real interest rates allow the fiscal consolidation programme to be implemented gradually without undue disruption to the growth recovery, while avoiding the risk of a debt crisis, hyperinflation, and a sovereign default.